Comparison Between Swenson and Soave Pull-Through in Hirschprung Disease - Leily Mohajerzadeh (Shiraz University of Medical Sciences, 2015)
Background Considerable controversy exists regarding the optimal surgical technique for the treatment of Hirschsprung disease. Currently, both Swenson and Soave procedures are used for its treatment. Objectives The purpose of this study was to compare outcomes and complications of Swenson and Soave pullthrough using a matched case control analysis. Patients and Methods A cross-sectional study was done on patients with Hirschsprung disease (HD) admitted in Mofid Children’s hospital from 2006 to 2012. Children with HD who underwent Soave procedure and sufficient data to analyze were matched 1:1 to a Swenson study sample. Patients were matched with respect to gestational age (37 - 42 weeks), age of patient at pullthrough procedure, operation stages, level of aganglionosis (rectosigmoid, sigmoid, descending and transverse colon) and the presence of comorbidities (major cardiac, trisomy 21, and other syndromes). SPSS version 18.0 was used for statistical analysis. Descriptive statistics and the Chi-square test and Student t-test were used. P < 0.05 was considered as significant. Results Sixty patients (30 patients undergone Soave, 30 patients undergone Swenson) had adequate data for matching and analysis. Mean follow-up time was 3 years for both groups. Mean (SD) age of patients at the time of pullthrough procedure was 43.1 (35.6) months in Swenson group (range; 1 - 168) and 41.9 (49.6) months in Soave group (range; 1 - 132) (P value = 0.920). No significant differences were seen in mean (SD) operating time (Soave: 156.7 (59.0) minutes, Swenson: 134.3 (51.4) minutes) (P value=0.145). There were no significant differences between 2 groups with regard to operative time, hospital stay, early and late complications such as postoperative obstructive symptoms, enterocolitis, fecal incontinence, perianal abscess and fistula, anastomotic leakage, peritonitis, and pelvic abscess formation. Rate of complication was 47% for Soave group and 40% for Swenson group (P value = 0.795, risk ratio = 1.147). Conclusions There were no signiﬁcant differences in the early and late complications between Soave and Swenson pullthrough procedures.